Gratitude contemplation as a method to improve human well-being and physical functioning: theoretical review of existing research - Burzyńska, Bożena (Journal of Education, Health and Sport, 2018)
Research in positive psychology aims to find and develop diverse ways to improve human well-being and the psychophysical functioning (Fredrickson, 2008; Seligman, 2002; Sheldon & Lyubomirsky, 2006). As an example, the studies regard such concepts as positive emotions, character strengths or meaning in life. One of the most frequently studied constructs is also gratitude, that is regarded as the appreciation of all what is meaningful, as well as valuable, to oneself (Sansone & Sansone, 2010). Also, the social aspect of being grateful, and the effects of gratitude on one’s health and physical functioning, are frequently emphasized (McCullough, Kimeldorf & Cohen, 2008; Fox, Kaplan, Damasio and Damasio 2015; Algoe, Haidt & Gable, 2008). Among great amount of work about general gratitude already, there is still little research about gratitude contemplation, one of the exercises that enable a person experiencing gratitude in form of meditation. In this article, first I explain the meaning of the gratitude construct and its impact on peoples psychophysical state in general. Then, I analyze one of the newest gratitude activity, that is gratitude contemplation, its definition, the way of use and the results of recent empirical studies worldwide. Finally, I critically discuss the findings and conclude with future steps for further research on gratitude contemplation. I believe that the results and analysis presented in the article create a base for further research in the area of positive psychology.